Dynamic drivers of heat and moisture transport into the Arctic ... - Hauswirth, David (ETH Zurich, 2020)
The poleward flow of energy into the Arctic plays a fundamental role for thermodynamic processes and strongly influences synoptic weather features in the Arctic. In this study, we analyse atmospheric dynamical drivers of anomalous poleward latent heat transport in the Arctic. Besides, we study the influence of anomalous moisture transport on surface temperature, cloud cover and precipitation. The correlation between weekly zonal mean poleward heat transport and temperature anomalies at 70°N shows a strong seasonal variation with moderate correlation between November and March and only very little correlation during summer. Analysing the relation between anomalous latent heat transport and synoptic weather features, we observed that from November till March the 10% most positive daily zonal mean latent heat transport at 70°N are linked to strong positive cyclone anomalies over the Greenlandic east coast as well as positive blocking anomalies to the west of Scandinavia. These anomalous transports further lead ...